Nano-Enabled Insecticides for Efficient Pest Management: Definition, Classification, Synergistic Mechanism, and Safety Assessment - Ying Wei; Jingyi Chen; Min Dong; Meizhen Yin; Jie Shen; Le Gao; Shuo Yan (Nanomaterials, 2025)
The widespread use of pesticides plays a vital role in safeguarding crop yields and ensuring global food security. However, their improper application has led to serious challenges, including environmental pollution, pesticide residues, and increasing insect resistance. Traditional chemical pesticides are no longer sufficient to meet the demands for sustainable modern agriculture. Recent advances in nanotechnology offer innovative strategies for improving pesticide delivery, bioavailability, and selectivity. This review systematically summarizes the current progress in nano-insecticides, including their definitions, classification, preparation techniques, synergistic mechanisms, insecticidal performance, and safety evaluation. In addition, emerging strategies, such as multi-stimuli responsive systems, co-delivery with multiple agents or genetic materials, and integration with biological control, are discussed. Finally, future perspectives are proposed to guide the design/development of intelligent, efficient, and eco-friendly nano-insecticides for sustainable pest management in modern agriculture.